KONSTRUKSI MAKNA PEREMPUAN DALAM IKLAN TELEVISI (Analisis Semiotika R. Barthes pada Iklan Televisi AXE Versi âHarga Minimâ) - , Febrimarani Malinda ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Axe is the body care products for men from Unilever. AXE ads are always showing beatiful women and men are also ideal for the iconic products. Ads in this AXE product to try to construct the meaning of women in an advertisement media to influence the reality of the imagery of women society. The use of female models in the ads contains a lot of ideology that was deliberately shown implicitly by the party advertisers. The phenomenon is what finally pushed the author to conduct research on how the meanings women in ads aired version of th AXE Effect âharga minimâ in Indonesiaâs private television aired the end of 2009-2010. The methods used in this study is the semiotics of Roland Barthesâs methods by giving an over view of the state or the status of womenâs imaging phenomena in society through AXE parfume ad version of âharga minimâ, and in women who dissect the construction of meaning constructed by television advertising media. By using the social construction of reality approach Peter L. Berger and Thomas Luckmann who brings the analysis to the construction of meaning that also reflect on the phenomenology of Alfred Schutz on the establishment of meaning constructed by social reality. With this semiotic analysis can help authors in finding the meanings hidden text the description of the ad includes visual and verbal aspects of the advertisements. The results showed that the messages conveyed in broadcast advertising AXE are showing that women construct meaning in the formation of the female characters are based on menâs favorite with all who look sexy, sensual and simple, even with things that look âminimalisâ will attract more attention. Women are always potrayed as objects in a display ad in which there is an element that accentuates the femaleside from the body untill her beautiful face as a messager product. Thus, forming a visible ideology is a life style , images of women in social class identity and affirmation pathriarchal values. This is the result of the construction of television advertising media on the meaning of women in the male product ads.